1999
DOI: 10.1021/jf990227h
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Colorimetric Determination of Azadirachtin-Related Limonoids in Neem Seed Kernel

Abstract: A colorimetric method was developed for the determination of total azadirachtin-related limonoids (AZRL) in neem seed kernel extracts. The method employed acidified vanillin solution in methanol for the colorization of the standard azadirachtin or neem seed kernel extracts in dichloromethane. Through the investigation of various factors influencing the sensitivity of detection, such as the concentration of vanillin, acid, and the time required for the formation of color, optimum conditions were selected to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 11 publications
1
46
0
3
Order By: Relevance
“…Due to its low cost as well as biocompatibility, neem extract is used as pesticide in agricultural field [8]. Azadirachtin, a tetranortriterpenoid, is the main active component of neem, which contains other active substances, such as salanin, epoxiazadiradione, meliantrol, melianone, gedunin, nimboline, nimbin, deacetilasalanin, azadiractol, azadirone, vilosinin, and meliacarpine, and over 300 characterized components [9][10][11][12]. Azadirachtin provides repellent, antihormonal, and antifeedant properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its low cost as well as biocompatibility, neem extract is used as pesticide in agricultural field [8]. Azadirachtin, a tetranortriterpenoid, is the main active component of neem, which contains other active substances, such as salanin, epoxiazadiradione, meliantrol, melianone, gedunin, nimboline, nimbin, deacetilasalanin, azadiractol, azadirone, vilosinin, and meliacarpine, and over 300 characterized components [9][10][11][12]. Azadirachtin provides repellent, antihormonal, and antifeedant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Azadirachtin provides repellent, antihormonal, and antifeedant properties. Neem leaf works as pesticide by inhibiting enzyme activities of insects which govern growth [8,9] of insects. Three major enzymes, namely, prothoracicotropic hormone (PTTH), juvenile, and ecdysone [13], play an important role for the growth.…”
Section: Introductionmentioning
confidence: 99%
“…is a tree from the Meliaceae family originated from India. It is known for its pesticide activity against more than 400 insect pests (Siddiqui et al, 2003) and pharmacological activities, such as anti-inflammatory, anti-malaria, anti-fertility, antimicrobial (Subapirya & Nagini, 2005;Dai et al, 1999), anti-acne (Jain & Basal, 2003), acaricidal (Abdel-Shafy & Zayed, 2002), and nematicidal (Sharma et al, 2003). The plant is traditionally used in the Indian region and many of its activities have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…515) method [10][11][12] . The chromatographic determination of Aza from different PNF samples was achieved using a C-18 analytical column with a water-acetonitrile mixture (65 : 35) as the mobile phase (flow rate 1 ml/min; UV detector at 214 nm).…”
mentioning
confidence: 99%
“…Standard Aza has a reported half-life of 3.9 days when exposed to UV light 11 . Thus, it can be concluded that Aza in its natural form in PNF is more stable under UV radiation than the pure isolated Aza.…”
mentioning
confidence: 99%